“Evaluación etológica del comportamiento canino bajo distintos colores en el cantón Latacunga”. - Jiménez Utreras, Andrea Celina (2024)
In recent years, constant canine behavior problems have been evident, such as attacks by dogs on veterinary professionals and the general public, as well as problems with nervousness and even lack of attention from dogs to their guardians. From the ethological point of view, the dog’s temperament and behavior depends largely on the contribution of its guardian, which, when it is not adequate is reflected in a problem of aggression and nervousness, that is why the use of different colored items is proposed. Prior to an evaluation through ethograms and socialization of results allow the distinction of canine behavior, thus facilitating management in veterinary centers and their usual environment. Therefore, sampling was carried out at the “Zoocat” Veterinary Clinic in the Latacunga Canton, Cotopaxi Province, with a total of 104 individuals sampled, where the ethograms applied to each patient were recorded by categories, in addition to considering variables such as: age, race, reproductive status, environment and background; its respective additive was assigned: green for a dog with stable behavior, yellow for nervous or anxious behavior, and red for aggressive or dominant behavior. As a result, 70% of the total numbers of individual evaluated belong to stable animals, 15% to nervous animals and 15% to aggressive animals, strongly affirming that the behavioral development of canines depends on all the care and resources offered by their guardian. That is why a more in-depth study and the dissemination of this evaluation’s types in veterinary centers and campaigns that raise public awareness about pet care becomes a fundamental tool to avoid canine behavior problems, in addition of providing an environment of healthy coexistence between man and canine.